Self-confidence of personality and the level of self-actualization of the employees of commercial organizations - I A Novikova; G N Zamaldinova (Peoples' Friendship University of Russia (RUDN University), 2010)
The article is devoted to the analysis of the results of empirical research of self-confidence as a system-functional feature of the personality (according to A.I. Krupnov) in correlation with the level of self-actualization of the employees of commercial organizations.